Pengaruh Belanja Modal dan Pegawai Terhadap Pertumbuhan Ekonomi NTB Dimoderasi Realisasi Anggaran - Fitri Fitri; Ikrawati Ikrawati; Wahyu Hasdi; Muhammad Ikram S; Nurfadilah Nurfadilah (Sekretariat Pusat Lembaga Komunitas Informasi Teknologi Aceh, 2026)
This study aims to analyze the influence of capital expenditure and employee expenditure on regional economic growth in the Province of West Nusa Tenggara (NTB) and to examine the role of budget realization as a moderating variable. The research employs a quantitative method using panel data from eight districts/municipalities in NTB for the period 2020–2024. Data analysis was conducted using multiple regression and Moderated Regression Analysis (MRA) to test the interaction between the independent variables and the moderating variable.The results indicate that capital expenditure has no significant effect on economic growth, whereas employee expenditure shows a positive and significant effect. Budget realization does not moderate the influence of capital expenditure but is proven to strengthen the effect of employee expenditure on regional economic growth. These findings suggest that the effectiveness of capital expenditure utilization still needs improvement, while more productive management of employee expenditure can contribute significantly to regional economic activity. In addition, optimal budget realization serves as an important factor in supporting sustainable economic growth. This study recommends incorporating additional macroeconomic variables in future research to obtain a more comprehensive understanding of the determinants of economic growth in NTB.